Melting diamond in the diamond cell by laser-flash heating. Issue 1 (2nd January 2023) - Yang, L.; Karandikar, A.; Shiell, T. B.; Cook, B. A.; Wong, S.; Field, M. R.; Bradby, J. E.; Haberl, B.; McCulloch, D. G.; Boehler, R.
ABSTRACT: The phase behavior of carbon at high pressure and the search for carbon structures denser than diamond has been explored for decades showing large discrepancies, with many fundamental questions remaining unresolved. Here we show evidence of melting above the graphite-diamond-liquid (GDL) triple point (∼13 GPa, 4000 K) up to 50 GPa on samples recovered from single flash-heating events using spectroscopic and electron microscopic methods. The results show that for all pressures, diamond melts below the triple point temperature contradicting previous studies, most of which predict a positive slope of the melting curve.